PENGARUH KECERDASAN INTELEKTUAL, PERILAKU BELAJAR, PERILAKU BUDAYA, DAN KEPERCAYAAN DIRI TERHADAP TINGKAT PEMAHAMAN AKUNTANSI - Nur Faidah Asholihah, Rispantyo & Djoko Kristianto (Universitas Slamet Riyadi, 2019)
This study aims to analyze the specification of the influence of intellectual intelligence, learning behavior, cultural behavior and self-confidence to the level of understanding accounting Faculty of Economics Slamet Riyadi University, Islamic University of Batik and Setia Budi University Surakarta. The research was conducted by survey with population of students of Faculty of Economics Slamet Riyadi University, Batik Islamic University and Setia Budi Surakarta University class of 2014 with sampling technique using simple random sampling that is random sample selection type and sample number 35 students. Data collection techniques using questionnaires. Data analysis techniques using classical assumption test, descriptive statistics, linear regression analysis, F test, t test and coefficient of determination. Result of validity and reliability test known that valid and reliable questionnaires and from classical assumption test obtained result that free data multicolinearity, free autocorelasi, did not happened heteroscedasticity and distributed data norm. Intellectual intelligence, learning behavior and cultural behavior have no significant effect on the level of understanding of accounting, while self-confidence significantly affects the level of understanding of accounting. Keywords: Intellectual intelligence, learning behavior, cultural behavior, confidence and understanding of student accounting.